(untitled) (Colección, 2017)
The aim of this article is to describe and explain the process of formulation and implementation of security policies in Province of Buenos Aires between 1984 and 2011. The central hypotheses considers that: a) governors are the actors with capacities and interests to pursue a policy of security of left or right according to their plan of campaign, which responds to other factors which are not the alleged police interests: mainly the ideology of the national executive and the location of the median voter; b)the bureaucratic compliance with security policies formulated by governors increase in contexts where he is aligned with the national executive. The corroboration of those hypotheses instructs on the strategic game behind security policies and the relative autonomy of the police and the penal system in Buenos Aires.